Determinants of prolonged hospitalization and mortality among leptospirosis patients attending tertiary care hospitals in northeastern state in peninsular Malaysia: A cross sectional retrospective analysis - Al Hariri, Yassin K.; Sulaiman, Syed A. S.; Khan, Amer H.; Adnan, Azreen S.; Al-Ebrahem, Sundos Q. (Frontiers in Medicine, 2022)
Leptospirosis is the most common anthropozoonosis worldwide and imposes a major public health problem in many tropical countries. It is a leading cause of disease burden in form of mortality, morbidity, and hospital admission. Identifying patients at high risk for mortality or for prolonged hospitalization may save lives and preserve the economy. The aim of the current study is to identify significant factors associated with disease mortality and prolonged hospitalization. A cross-sectional retrospective study in two tertiary care teaching hospitals in Kelantan, Peninsular Malaysia was conducted and included adult patients proven to have leptospirosis depending on IgM ELISA. Patients were classified into two classes depending on prolonged hospitalization (>7 days or ≤ 7 days) and mortality (fatal cases or non-fatal cases). Patients’clinico-laboratory data were compared according to these two outcomes using the appropriate statistical test. Of the 525 patients enrolled, 136 (25.9%) had prolonged hospitalization. The mean length of stay was 6.77 ± 5.68 days. Logistic regression analysis identified acute kidney injury (AKI) (OR 2.3), Jaundice (OR 2.7), elevated alanine aminotransferase (ALT) (OR 2), and prolonged prothrombin time (PT) (OR 1.9) independently associated with prolonged hospitalization. The case fatality rate was 6.48% and around one-third of fatal cases had prolonged hospitalization of more than seven days. Factors associated with leptospirosis mortality included age > 40 years (p<0.001), patients presented with tachypnea (p=0.002), pulmonary infiltrate (p<0.001), T-wave changes (p<0.001), atrial fibrillation (p=0.013), conducting abnormality (p<0.001), chronic kidney diseases (p<0.001), multiple organ dysfunctions (p<0.0010), respiratory failure (p<0.001), pneumonia (p<0.001), sepsis (p=0.004), low venous PH (p=0.042), AKI (P<0.001), elevated AST (p<0.001) or ALT (p=0.004), hypoalbuminemia (p<0.001), rhabdomyolysis (p<0.001), severe thrombocytopenia (p=0.042), prolonged PT (p<0.001) or prolonged aPTT (p<0.017). A significant proportion of leptospirosis patients (25.9%) had prolonged hospital stay and less proportion died (6.48%). Early identifying patients with factors associated with prolonged hospitalization and death will positively impact practitioners’ decisions regarding the proper and fast course of management including ICU admission